Perlindungan Hukum Akibat Kerugian Transaksi Aplikasi Mobile Banking Bagi Nasabah Perbankan Berdasarkan Hukum Perbankan - Danendra Aryasatya Maheswara; Yusrul Hana (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The advancement of technology in the banking sector has encouraged the adoption of mobile banking applications as a fast and efficient means of transaction for customers. However, this convenience is accompanied by the risk of losses for customers due to cybercrimes, such as data theft and unauthorized transaction access. This study aims to analyze the legal protections available for banking customers who experience losses from transactions through mobile banking applications and to examine the relevant provisions in banking law. The research employs a normative juridical approach, analyzing regulations, legal literature, and related cases. The results indicate that, although a legal framework exists to protect customers, there are still weaknesses in its implementation, which prevent customers from consistently receiving maximum protection. This study recommends strengthening regulations and enhancing transparency in the process of addressing customer losses to create a safer and more reliable digital banking ecosystem.